ANALISIS PENENTUAN HARGA POKOK PRODUKSI BERDASARKAN SISTEM ACTIVITY BASED COSTING PADA USAHA TEMPE PAK ALI DI SAMARINDA - TITIK YUNI PUSPITA SARI (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
The formulation of the problem in this study is to find out how much the basic price per pack of tempe in the Tempe Pak Ali business if calculated using conventional methods and activity based costing method, what factors cause differences in the cost of production based on the system activity based costing with conventional methods in Mr. Ali's Tempe Business. The research method used is descriptive research with a quantitative approach. The type of primary data obtained from interviews and direct observations on the Tempe Pak Ali Business. The results of this study are the cost of tempe production based on the activity based costing system of Rp. 8632.66 and conventional system based of Rp. 9,389.41. The conclusion of this study is the difference that occurs in determining the cost of production used by Tempe Pak Ali's Business with the activity based costing method due to the imposition of overhead costs produced by making tempe and conventional methods and ABC methods are different, so that the costs obtained can be greater or more small. The activity based costing method can be applied to Pak Ali's Tempe Business because using the ABC method requires lower costs than using conventional methods.